Unraveling the role of surface mucus-binding protein and pili in muco-adhesion of Lactococcus lactis. - Doan Thanh Lam Le (Public Library of Science (PLoS), 2013)
Adhesion of bacteria to mucus may favor their persistence within the gut and their beneficial effects to the host. Interactions between pig gastric mucin (PGM) and a natural isolate of Lactococcus lactis (TIL448) were measured at the single-cell scale and under static conditions, using atomic force microscopy (AFM). In parallel, these interactions were monitored at the bacterial population level and under shear flow. AFM experiments with a L. lactis cell-probe and a PGM-coated surface revealed a high proportion of specific adhesive events (60%) and a low level of non-adhesive ones (2%). The strain muco-adhesive properties were confirmed by the weak detachment of bacteria from the PGM-coated surface under shear flow. In AFM, rupture events were detected at short (100-200 nm) and long distances (up to 600-800 nm). AFM measurements on pili and mucus-binding protein defective mutants demonstrated the comparable role played by these two surface proteinaceous components in adhesion to PGM under static conditions. Under shear flow, a more important contribution of the mucus-binding protein than the pili one was observed. Both methods differ by the way of probing the adhesion force, i.e. negative force contact vs. sedimentation and normal-to-substratum retraction vs. tangential detachment conditions, using AFM and flow chamber, respectively. AFM blocking assays with free PGM or O-glycan fractions purified from PGM demonstrated that neutral oligosaccharides played a major role in adhesion of L. lactis TIL448 to PGM. This study dissects L. lactis muco-adhesive phenotype, in relation with the nature of the bacterial surface determinants.